2016
DOI: 10.1016/j.btre.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of biosurfactant production by Bacillus brevis using response surface methodology

Abstract: The present study aims to evaluate and validate a statistical model for maximizing biosurfactant productivity by Bacillus brevis using response surface methodology. In this respect, twenty bacterial isolates were screened for biosurfactant production using hemolytic activity, oil spreading technique, and emulsification index (E24). The most potent biosurfactant-producing bacterium (B. brevis) was used for construction of the statistical response surface model. The optimum conditions for biosurfactant productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 27 publications
2
52
0
4
Order By: Relevance
“…The effect of temperature, pH, incubation period, and glucose concentration were evaluated [44]. Emulsion reached 73%.…”
Section: Central Composite Designmentioning
confidence: 99%
“…The effect of temperature, pH, incubation period, and glucose concentration were evaluated [44]. Emulsion reached 73%.…”
Section: Central Composite Designmentioning
confidence: 99%
“…According to described by [16] oil spreading was evaluated by adding 20 mL distilled water on a Petri dish followed by addition of 50 µL of oil to its surface.…”
Section: Application Of Crude Biosurfactant In Oil Spreadingmentioning
confidence: 99%
“…According to their compositions, surface tension is able to be decreased by surfactants. These compounds play many rolls of human life in many fields not only agricultural, cosmetic, pharmaceutical applications, but also in food industries [1]. However, the synthetic chemical surfactants are toxic and difficult to degrade [2].…”
Section: Introductionmentioning
confidence: 99%
“…Mouafi et al [1] reported that lipopeptide biosurfactant production from Bacillus brevis was increased by glucose supplementation in medium. The lipopeptide biosurfactant yield of Bacillus subtilis B20 was increased to 2.29 g/L when cultured with molasses [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation